سورۃ یسین کا اردو ترجمہ اور مولانا عبدالہادی شاہ منصوری کی تفسیر البرھان فی مشکلات القرآن کے تناظر میں: Translation and Interpretation of Surah-e-Yaseen in the Light of Tafseer "Al-Burhan Fi-Mushkilat-ul-Quran" of Molana Abdul Hadi Shah Mansoori (R.A) - Abdul Basit; Dr. Ishfaq Ali (International Research Journal of Arabic and Islamic Studies, 2024)
Alhamdulillah, Lord of the worlds, and prayers and peace be upon the last of the Prophets and Messengers. He continued the series. Allah Ta'ala has been choosing this special and chosen servant as a messenger or a prophet among humans, who used to be superior to all humans present at that time in terms of their characters and speech. And at the same time, HE has been sending now a scripture for a book as a rule of life. Therefore, the chain of prophethood that started with prophet Adam Ali Nabina and peace be upon him ended with Hazrat Muhammad Ali Nabina. Have we been sent by Allah Almighty as the last messenger to guide mankind? You have also been given a book for human guidance according to the Sunnah of God, which is known to the whole world as "Quran Majeed". The Holy Quran is the last divine book revealed by Allah SWT for the guidance of mankind. The Quran was revealed in pure Arabic language. But being principled, most of it needs interpretation and explanation. Allah Ta'ala has given for Rasulullah Alayhi a position of honour that he will recite the Qur'an as well as explain it. This is the reason why most of the books of Hadiths have a permanent chapter containing commentry traditions. If we look at the interpretation of the Holy Qur'an, then the Muslim Ummah has given proof of full responsibility. First of all this, the companions dedicated their lives for the great work. He passed on all the traditions to his disciples that were related to Tafseer. Therefore, great commentators were born among his students. Among them, Maulana Abdul Hadi aka Shah Mansoor Babaji, a famous and brilliant personality as a commentator, who was born in 13th century Hijri, and who at that time started teaching the interpretation of the Qur'an in the present Khyber Pakhtunkhwa province (formerly North-West Frontier Province) at that time. In the research paper under consideration, an effort is made to clarify the exegesis of Hazrat Sheikh, to mention the rules and regulations that the Sheikh used to explain during the exegesis. Here, an attempt is also made that Hazrat Sheikh's commentary, Manbij Jamhoor, what is compatible with it, what their peculiarities are, similarly the Sheikh Sahib's style of reasoning and inference are also discussed, and all the materials related to Hazrat Sheikh Sahib's commentary are presented together in a book form.